Simulation in Nursing Education-International Perspectives and Contemporary Scope of Practice - Kelly, Michelle; Berragan, E.; Husebø, S.; Orr, F. (Sigma Theta Tau International. Honor Society of Nursing, Inc., 2016)
Purpose: This article provides insights and perspectives from four experienced educators about their approaches to developing, delivering, and evaluating impactful simulation learning experiences for undergraduate nurses. A case study format has been used to illustrate the commonalities and differences of where simulation has been positioned within curricula, with examples of specialized clinical domains and others with a more generic focus. The importance of pedagogy in developing and delivering simulations is highlighted in each case study. A range of learning theories appropriate for healthcare simulations are a reminder of the commonalities across theories and that no one theory can account for the engaging and impactful learning that simulation elicits. Clinical Relevance: Creating meaningful and robust learning experiences through simulation can benefit students' performance in subsequent clinical practice. The ability to rehearse particular clinical scenarios, which may be difficult to otherwise achieve, assists students in anticipating likely patient trajectories and understanding how to respond to patients, relatives, and others in the healthcare team. © 2016 Sigma Theta Tau International.